Saliamonas Antanaitis (1894–1973) and his research into the old mathematics - Banionis, Juozas (Lietuvos matematikos rinkinys, 2002)
Antanaitis is one of the 20th century Lithuanian professional mathematicians, who trained pedagogues at Teachers' Colleges in the 3–4th decades. After World War II S. Antanaitis worked in the Gymnasium of the 16th of February in Western Germany. He won distinction in research into mathematics. S. Antanaitis published articles on mathematics. There was a critique, some articles touching upon questions of methodology and mathematics history. Articles on mathematics history must be paid attention to because they threw the light both on the portraits of the famous creators in the period of elementary mathematics (until 17th century) and their merits in this scientific field. One of those articles was up for a famous astronomer and mathematician Johan Kepler (1571–1630). Another one was an original book about a scientist of Ancient Greece Archimedes (287 BC–212 BC). S. Antanaitis having made a thorough analysis of works of European science historians presented these science personalities and underlined importance of their works for the development of the higher mathematics.